2017
DOI: 10.3233/jad-161304
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Peripheral Immune System in Dementia

Abstract: Alterations in the immune response that result in inflammation might play a role in the pathology of dementias. In order to analyze changes of the peripheral immune system associated with different types of dementias, we determined several innate and adaptive cell populations in whole blood using flow cytometry. We included patients with Alzheimer's disease (AD; n = 60), vascular dementia (VaD; n = 20), and frontotemporal dementia (FTD; n = 12) at the time point of diagnosis and 24 age-matched neuropsychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 47 publications
3
56
2
Order By: Relevance
“…Moreover, this last team of authors reported that levels of activated HLA-DR-positive CD4 + and CD8 + T cells were significantly increased in the peripheral blood of AD and MCI patients compared with age-and sex-matched controls, but not in patients with a range of non-AD dementias [83]. This finding is consistent with that of other published research which indicates that the pattern of T cell abnormalities seen in AD may well be specific to the disease [87,88].…”
Section: Evidence Of Peripheral Immune Abnormalities In Adsupporting
confidence: 86%
“…Moreover, this last team of authors reported that levels of activated HLA-DR-positive CD4 + and CD8 + T cells were significantly increased in the peripheral blood of AD and MCI patients compared with age-and sex-matched controls, but not in patients with a range of non-AD dementias [83]. This finding is consistent with that of other published research which indicates that the pattern of T cell abnormalities seen in AD may well be specific to the disease [87,88].…”
Section: Evidence Of Peripheral Immune Abnormalities In Adsupporting
confidence: 86%
“…These findings support the hypothesis that AD pathophysiology may be related to salivary levels of Lf and the innate immune response to brain infections. Innate immune pathways are commonly activated in other neurodegenerative disorders [45][46][47][48]. Therefore, it is remarkable that salivary Lf levels will not decrease in other dementia such as FTD.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced neuroinflammatory process damages neurons and alters the (BBB). These mediators also induce peripheral inflammation and then return to further stimulate local neuroinflammation ( Blach-Olszewska et al, 2015 ; Festoff, 2016 ; Busse et al, 2017 ). This progressive pro-inflammatory situation is exacerbated with age, creating a vicious cycle of local and systemic inflammatory responses leading to activation of cytotoxic microglia, unbalanced cytokine production, Aβ accumulation and irreversible brain damage.…”
Section: How May All These Theories Be Reconciled?mentioning
confidence: 99%